Comparison of analytical sensitivity of automated microbiological blood culture systems - Lyamin A.V.; Ismatullin D.D.; Kozlov A.V.; Alekseev D.V.; Kayumov K.A.; Bochkareva P.V.; Antipov V.A. (Клиническая микробиология и антимикробная химиотерапия, 2024)
Objective.